TEKNIK KOMUNIKASI DAKWAH PIMPINAN CABANG MUHAMMADIYAH DALAM PEMBINAAN RANTING MUHAMMADIYAH DI METRO UTARA PERIODE 2015-2020 - Maimunah, Anis; Sabdo, Sabdo; Nur, Muhammad (DECODING: Jurnal Mahasiswa KPI, 2020)
The author gives the title of this undergraduate thesis communication techniques preaching the leadership of the Muhammadiyah branch in the guidance ofMuhammadiyah branches in the North Metro in the at 2015-2020 period. Da'wah is anobligation for every Muslim that must be done in order to spread the teachings of Islam.Inthis case, it is no less important to preach in organizations or society, because in anIslamic missionary organization can not be separated. Especially for people who arelacking in guidance propaganda. The research type is field research with a descriptiveanalytical approach. Data collection methods that researcher use is observation,interviews and documentation.The data were analyzed by sorting out the available datathen presented systematically and made conclusions. Based on the research results, itwas concluded that the communication technique on Da'wah Branch CommunicationMuhammadiyah North Metro is an informative communication technique that is to holdroutine recitation of branches and branches which are held once a month or three months.